2006
DOI: 10.1242/dev.02177
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaKnickkopf and Retroactive are needed for epithelial tube growth and cuticle differentiation through their specific requirement for chitin filament organization

Abstract: Precise epithelial tube diameters rely on coordinated cell shape changes and apical membrane enlargement during tube growth. Uniform tube expansion in the developing Drosophila trachea requires the assembly of a transient intraluminal chitin matrix, where chitin forms a broad cable that expands in accordance with lumen diameter growth. Like the chitinous procuticle, the tracheal luminal chitin cable displays a filamentous structure that presumably is important for matrix function. Here, we show that knickkopf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 42 publications
5
159
0
Order By: Relevance
“…Because the chitin matrix requires renewal during larval molting, we analyzed essential modulators for chitin maturation and protection. It was shown that newly synthesized chitin is protected by the conserved glycosylphosphatidylinositol-anchored Knk (Knickkopf) protein for organization of the body wall cuticle in Tribolium and for cuticle texture in Drosophila trachea and epidermis (4,24,25). In wild type first instar larvae, Knk was found in the cuticle matrix, showing strong co-localization with chitin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the chitin matrix requires renewal during larval molting, we analyzed essential modulators for chitin maturation and protection. It was shown that newly synthesized chitin is protected by the conserved glycosylphosphatidylinositol-anchored Knk (Knickkopf) protein for organization of the body wall cuticle in Tribolium and for cuticle texture in Drosophila trachea and epidermis (4,24,25). In wild type first instar larvae, Knk was found in the cuticle matrix, showing strong co-localization with chitin.…”
Section: Resultsmentioning
confidence: 99%
“…The antibodies used are ␣-Spectrin (1:10, mouse, Developmental Studies Hybridoma Bank), Knk (1:333; rabbit) (24), Obst-A (1:300; rabbit) (19), Serp (1:175; rabbit), and Verm (1:175; rabbit) (10). Primary antibodies were detected by secondary antibodies linked with fluorescent dyes (Dianova, Hamburg, Germany and Jackson ImmunoResearch Laboratories, West Grove, PA) and mounted in Vectashield (Vector Laboratories, Burlingame, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Knk has subsequently been found to be essential for the normal laminar organization of endocuticle at embryonic stages of growth (10). However, the possible contributions of Knk to postembryonic cuticle morphogenesis were unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The uniform expansion of tube diameter requires the formation of a transient luminal chitin-based matrix (Araujo et al, 2005;Moussian et al, 2006;Tonning et al, 2005;Devine et al, 2005) (reviewed by Swanson and Beitel, 2006) (see Fig. 6).…”
Section: From Branches To Functional Tubes: Regulating the Luminal Spacementioning
confidence: 99%